2021
DOI: 10.1093/jn/nxab142
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Body Composition, Systemic Inflammatory Response, and Clinical Outcomes in Patients Admitted to an Urban Teaching Hospital with COVID-19

Abstract: Background COVID-19 has been associated with cases of severe respiratory illness, admissions to intensive therapy units (ITUs), and high mortality rates. Objectives The aim of the present study was to examine the relation between computed tomography- body composition (CT-BC) measurements, systemic inflammation, and clinical outcomes in those with COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…It is likely that in such study collective body composition parameters have less influence on the clinical outcome than other influencing factors as, e.g., bacterial superinfection, thrombosis, embolism, or bleeding. However, the negative impact of sarcopenia on the clinical outcome in the healthy older population 11 , 46 , 47 is known, and effects of obesity 7 , 8 , reduced muscle mass 10 , or muscle quality 6 on COVID-19 patients have been described. Also, while no association for the FMR to IMV or time to death was found, Kottlors et al have described its use to predict ICU admission 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that in such study collective body composition parameters have less influence on the clinical outcome than other influencing factors as, e.g., bacterial superinfection, thrombosis, embolism, or bleeding. However, the negative impact of sarcopenia on the clinical outcome in the healthy older population 11 , 46 , 47 is known, and effects of obesity 7 , 8 , reduced muscle mass 10 , or muscle quality 6 on COVID-19 patients have been described. Also, while no association for the FMR to IMV or time to death was found, Kottlors et al have described its use to predict ICU admission 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, a loss of lean muscle mass over the disease period has been described 5 , and a better thoracic muscle quality has been shown to be a protective factor against hospitalization, invasive mechanical ventilation (IMV), and death 6 . Also, obesity has been found to be significantly associated with higher hospitalization rates, IMV, intensive care unit (ICU) admission, and death 7 , while visceral and muscular fat amounts were related to the probability of ICU admission 8 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent cohort study (n = 1071) comparing the effect of frailty on 30-day mortality in COVID-19 positive and COVID-19 negative older patients (> 65 years), reported that frailty made only a small contribution to the hazard of dying in patients admitted with COVID-19 [ 8 ]. Furthermore, independent of age, comorbidity including obesity, sarcopenia and systemic inflammation are also associated with worsened clinical outcomes [ 7 , 9 ]. At present, the basis of the relationship between age, frailty and clinical outcomes is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the prevalence of malnutrition was related to the number of comorbidities only for MNA but not for CONUT (data not shown), in partial disagreement with previous studies (32,36). As for BC, while obesity and increased FM have frequently been associated with disease severity, length of hospital stay, ICU admission, and death (3,20,(37)(38)(39)(40)(41)(42)(43)(44), only a few studies have yielded data on muscle wasting, low FFM, and appendicular skeletal muscle in COVID-19 patients (4,7,8,14); for instance, a low pectoralis muscle area was found to be a predictor of poor prognosis (45). According to the data of this study, low FFMI and low SMI (by BIA) were observed in 17% and 31% of the whole sample, respectively (no previous evidence is available in the literature), being more common in malnourished patients as identified by MNA.…”
Section: Discussionmentioning
confidence: 69%